Analisis Fungsi Komisi Pemilihan Umum Kabupaten Bengkulu Utara dalam Sosialisasi Pemilihan Bupati dan Wakil Bupati Tahun 2020 - Jayanti, Hevi Dwi; Zetra, Aidinil; Asrinaldi, Asrinaldi (Indonesian Democracy Research Center, 2023)
The election of the Regent and Deputy Regent in 2020 in the midst of a pandemic which resulted in socialization activities being delayed and there were several obstacles to delays in the implementation of the socialization, namely the PSBB which made it difficult for the KPU to gather the community to carry out election socialization. And what's more, in North Bengkulu Regency, there are many areas that are isolated and have poor infrastructure. Responding to this obstacle, North Bengkulu Regency KPU took quick steps to add a mode of implementation of the socialization, namely Door to Door socialization, which was carried out within 14 (fourteen) days before the D-day of the voting. The socialization was carried out by the Adhoc agency which only used assignment letters from the KPU without any SK from the KPU. This study aims to describe in detail the process of implementing community outreach by the KPU of North Bengkulu Regency in the midst of a pandemic; knowing the effectiveness of Door to Door socialization as a form of the effectiveness of the institution's function in the socialization function, this mode will be used as a new solutive mode in the socialization stage. The research method used is qualitative, in the form of a case study research type. Data collection techniques are in-depth interviews, as well as documentation. Selection of research informants using purposive sampling technique. The theory used is Institutional Effectiveness according to Christopher C Hood. The results of this study indicate that the implementation of socialization by North Bengkulu Regency KPU is effective only on participation tools, while 3 other tools namely regulations, incentives and law enforcement show ineffective results. Implementation of Door to Door socialization which is used as a new method, also gives ineffective results from the factor of resource capacity as seen from the culture of the system; and accountability factors as seen from the executive report